XX դարասկզբի իրանահայ մամուլը (համառոտ ակնարկ) - Մելիքեան, Դերենիկ (ՀՀ ԳԱԱ հրատ.)
Иранско-армянская пресса особенно выделяется в последние годы XIX и впервые два десятилетия XX века. В это время иранские армяне пережили ряд испытаний (особенно в период Конституционной революции 1905–1912 гг, коснувшихся также и армянской прессы). The 20th century Iranian-Armenian press is distinguished mainly in the first two decades of the century. In this time span the Iranian-Armenians were living critical moments particularly during the Persian Constitutional Revolution (1905–1912), when numerous consecutive reviews were being published, shedding light on the political as well as cultural-social aspects of life.
Keywords: Մամուլ